Corruption Verdict on Embezzlement of Village Funds in the Department of John Rawls's Fairness Perspective - Albri Labaka (Corruptio, 2025)
This article examines judicial authority in adjudicating village fund corruption, analyzing Decision Number 11/Pid.Sus-TPK/2023/PN through a normative juridical approach and John Rawls’s fairness perspective. While the Panel of Judges applied Article 3 of the Anti-Corruption Law, the three-year sentence is disproportionate given state losses of approximately IDR 1.95 billion, the Defendant’s public office, and the lack of restitution. The ruling highlights a tension between procedural legality and substantive justice, emphasizing the need for judges to exercise social sensitivity, apply public reason, and consider the socio-structural impact on vulnerable communities. A holistic approach ensures that judicial decisions are legally valid, ethically sound, and socially responsive, reinforcing the moral authority of the courts and protecting marginalized groups.